2023
DOI: 10.3389/fgene.2023.1212228
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and dose escalation of intracerebroventricular CLN5 gene therapy in sheep supports clinical translation for CLN5 Batten disease

Nadia L. Mitchell,
Samantha J. Murray,
Martin P. Wellby
et al.

Abstract: CLN5 neuronal ceroid lipofuscinosis (NCL, Batten disease) is a rare, inherited fatal neurodegenerative disorder caused by mutations in the CLN5 gene. The disease is characterised by progressive neuronal loss, blindness, and premature death. There is no cure. This study evaluated the efficacy of intracerebroventricular (ICV) delivery of an adeno-associated viral vector encoding ovine CLN5 (scAAV9/oCLN5) in a naturally occurring sheep model of CLN5 disease. CLN5 affected (CLN5−/−) sheep received low, moderate, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that delivery of CLN5 gene therapy to the CLN5 −/− sheep brain via ICV administration alone is sufficient to halt or slow disease onset and progression, intracranial volume loss, and ameliorate disease pathology ( Mitchell et al, 2018 ; Mitchell et al, 2023a ). The results of this study indicate a dose-dependent transduction efficiency and correlated improved efficacy with the high ICV dose in the early and advanced symptomatic sheep as compared with the moderate dose evaluated in the pre-symptomatic animals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that delivery of CLN5 gene therapy to the CLN5 −/− sheep brain via ICV administration alone is sufficient to halt or slow disease onset and progression, intracranial volume loss, and ameliorate disease pathology ( Mitchell et al, 2018 ; Mitchell et al, 2023a ). The results of this study indicate a dose-dependent transduction efficiency and correlated improved efficacy with the high ICV dose in the early and advanced symptomatic sheep as compared with the moderate dose evaluated in the pre-symptomatic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analyses of CNS tissues demonstrated far fewer CLN5-positive cells in the pre-symptomatic treated cohort, reflecting their lesser ICV dose. Previous attempts at a moderate dose ICV delivery (2.4 × 10 11 vg) in 9-month-old CLN5 −/− sheep with advanced disease symptoms resulted in only one animal responding favorably ( Mitchell et al, 2023a ). In the current study, however, a higher dose was administered to symptomatic sheep, and all three of the early symptomatic treated sheep and two of the three advanced symptomatic treated sheep were clinically stable at 24 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations